Tahsin al-Kitabah and al-Khat al-Araby Learning Innovations in the Digital Era - Hasbullah, Abdur Ro'uf; Makhisoh, Iis (Asalibuna, 2023)
The emergence of various kinds of technological tools, digital media, and social media are making learning easier, by using online correction systems both in learning Tahsin al-Kitabah and Khat Araby. Apart from that, there are many applications related to khat learning, such as kitabahku, Mashq, Ana Mukhtariful khat, Kelk, and other applications that not only support students in learning Khat but also support the development of their creativity in creating work. This requires educators to utilize digital media as a medium to support learning. The implementation of Tahsin al-Kitabah learning using the "Abajadun" method and also learning Khat Araby using Manhaj Hamidi have their respective advantages. The Abajadun method emphasizes understanding the keys of mufrodat and murokkab using the keys of alif, ba', jim, and dal. Meanwhile, Manhaj Hamidi uses a tiered system from easy types of khat to difficult types of khat. And one of the advantages is the Khat Diploma as a standardization of the Sanad system. Both methods are innovative learning methods based on digital media because the learning process also uses digital technology as a learning support. The results show an increased effectiveness of khat learning. Even though in practice, there are several problems, efforts to improve and improve the quality of learning must still be made. Meanwhile, the use of digital-based applications such as Kitabahku and also digital-based guidebooks is a learning model that uses a Learning Visualization approach because students are greatly helped in the learning process by understanding the writing of Tahsin al-Kitabah and Khat Araby. Third, using the Mashq, Ana Mukhtarif al-Khat, and Kelk applications, is one of the strategies and approaches using the Active Learning model, where students are also actively involved in learning using these media both for practice and the work process. So, they can master calligraphy from basic to advanced level and be able to work well using manual or digital media.